The Effect of Grain Size on Microwave Interaction of Magnetite Concentrate Mixed with Carbonized Biomass Waste - Öztürk, Elif A.; Boyrazli, Mustafa; Turan, Mehmet Deniz; Erdemoğlu, Murat (Current Physical Chemistry, 2020)
Aims: In this study, microwave interaction of magnetite ore concentrate which was mixed with carbonized biomass waste and divided into different grain sizes, was studied. Materials and Methods: The mixture consisting of magnetite concentrate and carbonized product was pelletized by the addition of molasses and jelly as binders. The pellets prepared with various particle size powders were subjected to microwave treatment at different times. Results: Temperature of the pellet produced with powders between -212 +150 μm grain sizes and -45 μm were measured as 837.5°C at 304th second and 945.9°C at 210th second respectively. Conclusion: Although there was a large temperature difference between the core and the surface of the pellet, a high degree of metallization was observed in these samples.
Keywords: different grain sizes